Multifunctional Coatings of Titanium Implants Toward Promoting Osseointegration and Preventing Infection: Recent Developments - Lu, Xiaoxuan; Wu, Zichen; Xu, Kehui; Wang, Xiaowei; Wang, Shuang; Qiu, Hua; Li, Xiangyang; Chen, Jialong (Frontiers in Bioengineering and Biotechnology, 2021)
Titanium and its alloys are dominant material for orthopedic/dental implants due to their stable chemical properties and good biocompatibility. However, aseptic loosening and peri-implant infection remain problems that may lead to implant removal eventually. The ideal orthopedic implant should possess both osteogenic and antibacterial properties and do proper assistance to in-situ inflammatory cells for anti-microbe and tissue repair. Recent advances in surface modification have provided various strategies to procure the harmonious relationship between implant and its microenvironment. In this review, we provide an overview of the latest strategies to endow titanium implants with bio-function and anti-infection properties. We state the methods they use to preparing these efficient surfaces and offer further insight into the interaction between these devices and the local biological environment. Finally, we discuss the unmet needs and current challenges in the development of ideal materials for bone implantation.